Students’ Literacy Quality in Bahasa Indonesia: Attitude, Interest, and Functional Reading - Chuzaimah D. Diem; Mulyadi Eko Purnomo; Sofendi Sofendi (Jurnal Bahasa dan Sastra, 2017)
Abstract: The purpose of this research was to find out the literacy quality of junior high school (JHS) students in Palembang. To achieve the goal, a survey on students’ reading literacy achievement in relation to their attitude towards and interest in reading bahasa Indonesia (BI) as National Language was conducted. To collect the data, the Functional Reading Achievement Test (FRAT) and the questionnaire of Attitude Towards and Interest in Reading Literacy (ATIReaL) were distributed to 191 students. Then to know about the perception of the stakeholders on literacy education, a set of Literacy Education Questionnaire (LEQ) was also filled in by 136 parents, 132 teachers, 31 principals, 32 librarians, and 44 superintendants. In addition, some representatives of the stakeholders were also interviewed to see what they have done and would like to do in terms of students’ literacy education enhancement. The results showed that (1) students’ functional reading achievement (FRA) is on average level, 57.20; (2) there are some aspects of ATIReaL correlated significantly with students’ FRA; and (3) most of the stakeholderss agree that literacy education of JHS students need to be developed and enhanced by having appropriate programs and facilities based on national standards of education. Key words: bahasa Indonesia, functional reading, junior high school students, literacy education, reading attitude, reading interest   Abstrak:  Tujuan dari penelitian ini adalah untuk mengetahui kwalitas literasi dari peserta didik Sekolah Menegah Pertama (SMP) di Palembang. Untuk menemukan jawabannya, dilakukan survey pada kemampuan literasi membaca para siswa yang berhubungan dengan sikap terhadap membaca dan minat mereka dalam Bahasa Indonesia sebagai bahasa nasional. Functional Reading Achievement Test (FRAT) dan angket Attitude Towards and Interest in Reading Literacy (ATIReaL) diberikan kepada 191 siswa. Kemudian, untuk mengetahui persepsi para pimpinan mengenai pendidikan literasi, angket Literacy Education Questionnaire (LEQ) diberikan kepada 136 wali murid, 132 guru, 31 kepala sekolah, 32 pustakawan, dan 44 pengawas. Wawancara juga dilakukan kepada perwakilan pimpinan untuk mengetahuai apa yang telah and akan mereka lakukan untuk meningkatkan pendidikan literasi peserta didik. Hasil penelitian menunjukkan bahawa (1) pencapaian membaca fungsional para peserta didik berada pada tingkat menengah, 57.2; (2) ada beberapa aspek dari ATIReaL yang berhubungan secara signifikan terhdap FRA para peserta didik: (3) dan pada umumnya para pemimpin menyetujui bahwa pendidikan literasi siswa SMP perlu dikembangkan dan ditingkatkan melalui program dan fasilitas yang sesuai berdasarkan standar nasional pendidikan.  Kata-kata kunci:  bahasa Indonesia, membaca fungsional, siswa SMP, pendidikan literasi, sikap baca, minat baca